SISTEM INFORMASI PENYEWAAN KONTRAKAN BERBASIS WEBSITE DI KABUPATEN BULUKUMBA - Wahab, Zaskia Darajat; Hendryadi, Dedy; Halik, Sri Asfirawati (journal Informatika, Multimedia, dan Informasi, 2025)
This research aims to: (1) Design a website-based rental information system in the Bulukumba city area. (2) Implementing a website-based rental information system in the Bulukumba city area. (3) Knowing the response of users of the website-based rental information system in the Bulukumba city area. The research method used in this research is the System Development Life Cycle (SDLC) method with the Waterfall Model. It has several stages, namely: requirements analysis, design, implementation, testing, and maintenance. The data collection used was: Interviews, Literature Study and Documentation. The results of this research are: (1) This website-based rental information system was designed using the Unified Modeling Language (UML) and programmed using the PHP programming language so that it can make it easier and faster for customers to search for rentals. (2) Result of implementing a website-based rental information system in Bulukumba district, that is, with this website, it can provide fast service to potential customers when they want to rent a rental. (3) The results of testing the use of the system using a Likert scale obtained a score of 89.7% from 20 respondents, which is very positive.